Exploring the critical role of PANoptosis in the pathogenesis of intervertebral disc degeneration: mechanisms and potential therapeutic targets - Zhou, Kaisheng; Zou, Mingyang; Wu, Shaobo; Song, Wei; Dong, Hao; Dong, Yanbo; Zhang, Haihong (Frontiers in Cell and Developmental Biology, 2025)
Intervertebral disc degeneration (IVDD), a leading cause of chronic low back pain, imposes a significant global health burden due to its association with aging, inflammation, and mechanical stress. Emerging evidence highlights programmed cell death (PCD) as a pivotal driver of IVDD progression. PANoptosis, a novel integrated cell death mechanism combining pyroptosis, apoptosis, and necroptosis, has recently gained attention for its role in amplifying inflammatory responses and accelerating disc degeneration. This review synthesizes current knowledge on PANoptosis in nucleus pulposus cells (NPCs), emphasizing its regulatory crosstalk via multiprotein complexes and signaling pathways such as RIPK, caspase activation, and gasdermin-mediated membrane permeabilization. Key triggers, including oxidative stress, cytokine dysregulation, and mechanical compression, exacerbate PANoptosis, leading to NPC loss and extracellular matrix degradation. While therapeutic strategies targeting PANoptosis-related molecules show promise in preclinical studies, clinical translation remains limited. Elucidating the interplay between PANoptosis and other pathological pathways could unveil novel biomarkers and therapeutic targets. This review underscores PANoptosis as a critical axis in IVDD pathogenesis and advocates for multidisciplinary approaches to bridge mechanistic insights into effective clinical interventions.